Clinical Breast MR Using MRS or DWI: Who Is the Winner? - Sardanelli, Francesco; Carbonaro, Luca Alessandro; Montemezzi, Stefania; Cavedon, Carlo; Trimboli, Rubina Manuela (Frontiers in Oncology, 2016)
Magnetic resonance imaging (MRI) of the breast gained a role in clinical practice thanks to the optimal sensitivity of contrast-enhanced (CE) protocols. This approach, firstly proposed thirty years ago and further developed as bilateral highly spatially resolved dynamic study, is currently considered superior for cancer detection to any other technique. However, other directions than CE imaging have been explored. Apart from morphologic features on unenhanced T2-weighted images, two different non-contrast molecular approaches were mainly run in-vivo: proton MR spectroscopy (1H-MRS) and diffusion-weighted imaging (DWI). Both approaches have shown aspects of breast cancer hidden to CE-MRI: 1H-MRS allowed for evaluating the total choline peak (tCho) as a biomarker of malignancy; DWI showed that restricted diffusivity is correlated with high cellularity and tumor aggressiveness. Secondary evidence on the two approaches is now available from systematic reviews and meta-analyses, mainly considered in this article: pooled sensitivity ranged 71%-74% for 1H-MRS and 84%-91% for DWI; specificity 78%-88% and 75%-84%, respectively. Interesting research perspectives are opened for both techniques, including multivoxel MRS and statistical strategies for classification of MR spectra as well as diffusion tensor imaging (DTI) and intravoxel incoherent motion (IVIM) for DWI. However, when looking at a clinical perspective, while MRS remained a research tool with important limitations such as relatively long acquisition times, frequent low quality spectra, difficult standardization and quantification of tCho tissue concentration, DWI has been integrated in the standard clinical protocols of breast MRI and several studies showed its potential value as a stand-alone approach for breast cancer detection.